Torque Teno Virus load in lung cancer patients correlates with age but not with tumor stage. - Dirk Stefani (Public Library of Science (PLoS), 2021)
Background Torque teno virus (TTV) is a ubiquitous non-pathogenic virus, which is suppressed in immunological healthy individuals but replicates in immune compromised patients. Thus, TTV load is a suitable biomarker for monitoring the immunosuppression also in lung transplant recipients. Since little is known about the changes of TTV load in lung cancer patients, we analyzed TTV plasma DNA levels in lung cancer patients and its perioperative changes after lung cancer surgery. Material and methods Patients with lung cancer and non-malignant nodules as control group were included prospectively. TTV DNA levels were measured by quantiative PCR using DNA isolated from patients plasma and correlated with routine circulating biomarkers and clinicopathological variables. Results 47 patients (early stage lung cancer n = 30, stage IV lung cancer n = 10, non-malignant nodules n = 7) were included. TTV DNA levels were not detected in seven patients (15%). There was no significant difference between the stage IV cases and the preoperative TTV plasma DNA levels in patients with early stage lung cancer or non-malignant nodules (p = 0.627). While gender, tumor stage and tumor histology showed no correlation with TTV load patients below 65 years of age had a significantly lower TTV load then older patients (p = 0.022). Regarding routine blood based biomarkers, LDH activity was significantly higher in patients with stage IV lung cancer (p = 0.043), however, TTV load showed no correlation with LDH activity, albumin, hemoglobin, CRP or WBC. Comparing the preoperative, postoperative and discharge day TTV load, no unequivocal pattern in the kinetics were. Conclusion Our study suggest that lung cancer has no stage dependent impact on TTV plasma DNA levels and confirms that elderly patients have a significantly higher TTV load. Furthermore, we found no uniform perioperative changes during early stage lung cancer resection on plasma TTV DNA levels.